The Analysis of Sharia Financial Literacy Levels Among Teachers in Islamic Boarding School in Bungo Regency - Lailatul Karimah Karimah; Muhammad Zaki; Novita Eka Paradina (Talaa : Journal of Islamic Finance, 2025)
This study aims to describe the level and forms of Islamic financial literacy among teachers at Pondok Pesantren Al-Kautsar Babeko.  Islamic financial literacy is important in the Islamic boarding school environment because teachers play a role not only as educators but also as role models in applying economic principles of Islam in daily life.  This research used a qualitative approach with a case study method.  Data were obtained through in-depth interviews, observations, and documentation of several teachers who became research informants. Data analysis was carried out through stages of data reduction, data presentation, and conclusion drawing.  The findings showed that the teachers generally understand the basic concepts of finance, especially those based on Islamic principles, particularly in avoiding usury, gharar, and risky transactions.  However, some teachers still faced difficulties in managing finances in accordance with Islamic principles due to various obstacles.  Supporting factors for Islamic financial literacy included educational background in religion and teaching experience, while inhibiting factors include limited access to information and a lack of specific training in the field of Islamic finance.  These findings are expected to serve as input for Islamic boarding school managers and related stakeholders to improve the capacity of Islamic financial literacy among teachers.